The Influence of Concomitant Disorders on Disease Severity of Familial Mediterranean Fever in Children - Rabia Miray KIŞLA EKİNCİ and Sibel BALCI and Derya UFUK ALTINTAŞ and Mustafa YILMAZ (Archives of Rheumatology, 2018)
Objectives: This study aims to describe the effects of concomitant disorders on the course of familial Mediterranean fever (FMF) and the relevance of genotype on these associations. Patients and methods: Files of 494 FMF patients (257 males, 237 females; mean age 12.8±1.94 years; range 1.6 to 23 years) were retrospectively examined. Age of diagnosis, sex, MEditerrenean FeVer mutations, colchicine dosage, disease severity score and concomitant diseases in FMF course were recorded. FMF diagnoses were based on Tel-Hashomer criteria and disease severity was determined by international severity scoring system for FMF. Patients were divided into two groups as M694V positives and M694V negatives. We compared the groups in terms of accompanying illnesses, MEditerrenean FeVer mutations, and disease severity scores among five concomitant diseases: juvenile idiopathic arthritis (JIA), asthma, Henoch- Schonlein purpura, periodic fever, aphthous stomatitis, pharyngitis and adenitis syndrome, and others. Results: The mean age at diagnosis was 8.7±1.9 years. Eighty-five patients (17.2%) had accompanying diseases including JIA, asthma, periodic fever, aphthous stomatitis, pharyngitis and adenitis syndrome, and Henoch-Schonlein purpura. Mean disease severity scores were 2.4±1.1 in patients with only FMF and 3.0±1.5 in patients with concomitant disorders (p=0.001). Patients with concomitant JIA showed the highest severity scores (4.3±1.6). A statistically significant difference was found with one-way analysis of variance. Conclusion: Our findings indicate that concomitant diseases, particularly JIA, influence FMF severity. Therefore, it may be beneficial to focus on diagnosis and treatment of comorbid inflammatory diseases, which may worsen the course of FMF.